Analisis Penerapan Kerjasama Penanganan Terorisme Antara Indonesia Dan United Kingdom dengan Pendekatan Strategi 4 Pilar Kontra Terorisme - Lestari Sri Hutami; H Azhar; Nurul Aulia (Universitas Indo Global Mandiri, 2023)
Terrorism is a transnational crime that endangers world peace and security. The terrorist danger is imminent in Indonesia and the United Kingdom. One of the efforts to counter terrorism is by establishing international cooperation. The latest counter-terror cooperation carried out by BNPT is with The Homeland Security Mission of the United Kingdom of Great Britain and Northern Ireland. As a new collaboration, more in-depth studies are needed regarding the implementation of this work. Therefore, researchers conducted research related to the Implementation of BNPT RI Counter Terrorism Cooperation with The United Kingdom. The theory used is neoliberal institutional theory and the concept of counter terrorism. The concept of counterterrorism as defined by the United Kingdom CONTEST document in 2018 is utilized in this study to examine the research topic. The concept consists of four strategic pillars namely prevent, protect, prepare and pursue. The researcher’s finding confirmed that the collaboration was conducted in accordance with the agreement. The forms of activities that have been implemented are Joint Working Groups, visits to the Royal College of Defense Studies, Expert Group Meetings on Prevention of the Terrorist Use of the Internet and Joint Overseas Protect and Prepare Representative Meetings. The implementation of partnership to combat terrorism in line with the four pillars of the counter-terrorism framework namely prevent, protect, prepare, and pursue.